Internal bremsstrahlung spectrum accompanying 1S electron capture in decay of Fe 55, Cs 131, and Tl 204 - Biavati, M. H.; Jorge Nassif, Sonia; Wu, C. S. (American Physical Society, 1962)
Fil: Biavati, M. H. Columbia University; Estados Unidos